Thromboembolic Disease after Cervical Spine Surgery: A Review of 5, 405 Surgical Procedures and Matched Cohort Analysis. (August 2016) - Sebastian, Arjun S.; Currier, Bradford L.; Clarke, Michelle J.; Larson, Dirk; Huddleston, Paul M.; Nassr, Ahmad
Study Design: Retrospective matched cohort analysis. Objective: The majority of the literature on venous thromboembolism (VTE) after spine surgery is limited to studies of thoracolumbar surgery. Less is known regarding the incidence of VTE and associated risk factors following cervical spine surgery. Methods: A total of 5, 405 patients at our institution underwent cervical diskectomy, laminectomy, corpectomy, laminoplasty, or fusion between 1995 and 2012; 85 of the 5, 405 patients (1.57%) suffered either a DVT (55) or pulmonary embolus (51) within 30 days postoperatively. The cases were matched 1:2 to controls based on age, sex, and date of surgery. Data regarding multiple perioperative factors, demographics, and comorbidities was collected. Results: Several risk factors were identified for VTE. Significant medical comorbidities included chronic venous insufficiency (odds ratio [OR] = 3.40), atrial fibrillation (OR = 2.69), obesity (OR = 2.67), and ischemic heart disease (OR = 2.18). Staged surgery (OR = 28.0), paralysis (OR = 19.0), combined approach (OR = 7.46), surgery for infection (OR = 18.5), surgery for trauma (OR = 11.1), comorbid traumatic injuries (OR > 10), oncologic procedures (OR = 5.2), use of iliac crest autograft (OR = 4.16), two or more surgical levels (OR = 3.48), blood loss > 300 mL (OR = 1.66), and length of stay 5 days or greater (OR = 3.47) were all found to be risk factors for VTE ( p  < 0.05) in univariate analysis. Multivariate analysis found staged surgery (OR = 35.7), paralysis (OR = 7.86), and nonelective surgery (OR = 6.29) to be independent risk factors for VTE. Conclusions: Although the incidence of VTE following cervical spine surgery is low, we identified several risk factors that may be predictive. More aggressive approaches to prophylaxis and surveillance in certain patient populations may be warranted.